Volume de atividade física e qualidade de vida dos policiais militares - Oliveira, Luis Carlos Nobre de (2014)
The police officer demands for their activities a good physical fitness to attend their duties. However, physical inactivity and obesity are increasing in the world population, together with the chronic degenerative diseases and conditions of inadequate quality of life. In this way, the objective of this study was to evaluate the Physical FitnessLevel (PFL), the Body Mass Index (BMI) and quality of life of police officer and analyze the association between these variables. We evaluated 262 police officers 216 (82.4%) males and 46 (17.5%) females, with 37.0±7.1 years old. The officers answered the IPAQ (International Physical Activity Questionnaire) to assess the level of physical fitnessand the SF-36 quality of live questionnaire. For association analysis, it was used the chi-square test, considering p<0.05. The results showed the overall mean BMI 27.6±3.7 kg/m2 . The physical fitness level was classified: 1.9% (n=5) very active, 30.1% (n=79) active, 51.5% (n=135) irregularly active and 16% (n=43)sedentary. The quality of life,it was observed that an overall average of 70.7±20.2 points. The functional capacity (86.1±16.7) had the best result, while the general health (60.8±17) had the worst result. In conclusion, the study showed a high percentage (68%) classified as sedentary or insufficiently active (68%) and within the range that overweight and obese (75%), which may be affecting the general health these professionals. These results highlight and showed the need for educational programs and physical activity of health promotion context to control these risk factors and improve the quality of life of this population. Keywords: Quality of life; Motor Activity; Sedentary Lifestyle; Body Mass Index; Military.